"Back‐to‐Front" Indole and Carbazole Synthesis from N, N‐Bis‐(2‐bromoallyl)amines by Combining Carbolithiation Reactions with Gold‐Catalysis. Issue 21 (21st October 2022) - Muñoz‐Torres, Miguel A.; Martínez‐Lara, Fernando; Solas, Marta; Suárez‐Pantiga, Samuel; Sanz, Roberto
Abstract: The combination of organolithium chemistry with gold catalysis has enabled the development of a synthetic strategy for accessing polysubstituted indoles and carbazoles from readily available starting materials. This method is based on a "back‐to‐front" approach from ketopyrroles, generated by intramolecular carbolithiation of N, N ‐bis‐(2‐lithioallyl)amines that evolve into 3, 4‐bis(lithiomethyl)dihydropyrrole intermediates capable of reacting with carboxylic esters and Weinreb amides. These ketopyrroles have demonstrated to be excellent precursors of mono or bis(alkynols)pyrroles that, under gold‐catalysis, experience a benzannulation reaction providing access to regioselectively substituted indoles or carbazoles. Abstract :